Adsorption of indoor toxic gas by ionic liquid impregnated activated carbons - Rahman, N.A.A. (American Institute of Physics Inc., 2016)
Butylpyridinium thiocyanate BuPyrSCN ionic liquid was synthesized by metathesis and characterized. NMR spectrum has shown the BuPyr cation while FTIR has shown the SCN anion peak which confirms the structure of the synthesized ionic liquid. The ionic liquid was impregnated on activated carbon in order to enhance performance of sulfur dioxide adsorption compared to the non-impregnated raw activated carbon. Two types of activated carbons were used; activated carbon cylindrical granules and cloth. Different percentages of ionic liquid loading (1%, 10% and 20%) were applied. The capacity of the adsorbent for treatment of 10 ppm and 50 ppm SO2 was determined by breakthrough curve analysis whereby optimum breakthrough time was obtained. BuPyrSCN impregnated on activated carbon cloth have shown higher adsorption performance. Â© 2016 Author(s).